PERANCANGAN APLIKASI BROWSER PENCARIAN KEYWORD DENGAN MEMANFAATKAN FITUR SEARCH DI BERBAGAI WEBSITE MENGGUNAKAN METODE QUERY HASH JOIN PADA PERANGKAT ANDROID - Ari Kartanto Sinuhaji; Yolanda Y.P Rumapea; Darwis Robinson Manalu (Universitas Methodist Indonesia, 2018)
The internet is a medium of information that is very fast and efficient in disseminating information that can not be separated by distance and time. To search for data through the website, sometimes the user forgets the address of the website to be search for data so that the data sought is difficult to obtain and if finally obtained, it takes a long time to find the data. Therefore a system is built that will facilitate the user in searching data without having to fill in the URL address of the search website, users can choose which websites will be used as a source of data search. Applications that are built using the hash join method where this method alone can be used to join tables containing website data in a database so that the user can display the desired data based on the input entered into the application. The results of the searches obtained are contents that contain texts in the form of titles or contents of web pages that match the keywords that users enter when searching from selected websites. This content can be in the form of web pages, which can then be accessed directly within the application.